Determinan Generasi Z Menerapkan Gaya Hidup Halal Di Kota Padangsidimpuan - Muhammad Ikhsan Harahap; Nurul Izzah; Muhammad Ridwan (IAIN Langsa, 2022)
Indonesia's great potential in developing the halal industry has not been optimally utilized. This can be seen from the low output of the halal industry, halal certificates that have not been applied globally and low halal awareness. This study aims to determine the factors that influence Generation Z in Padangdidimpuan City to adopt a halal lifestyle. This research is a quantitative research using primary data. The research sample is Generation Z in Padangsidimpuan City as many as 200 respondents. Data analysis was performed using Smart PLS. The results of the study show that experience and family influence Generation Z in implementing a halal lifestyle in Padangsidimpuan City. Meanwhile, perception, culture and demographics do not affect Generation Z in implementing a halal lifestyle. Generation Z with families who instill Islamic values ​​tend to adopt a halal lifestyle that is in accordance with Islamic teachings. A good understanding of the benefits of a halal lifestyle will motivate Generation Z to adopt a halal lifestyle.